Penerapan Model Problem Based Learning untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa di Kelas VIII – A SMP Negeri 1 Stabat - Radika Ananda; Zul Amry (Pusat riset dan Inovasi Nasional, 2024)
This study aims to determine whether applying the Problem Based Learning model can improve the mathematical problem solving ability of students of class VIII-A SMP Negeri 1 Stabat on SPLDV. This research is a class action research conducted in two cycles. Each cycle consists of 2 meetings. The subjects in this study were students of class VIII-A SMP Negeri 1 Stabat totalling 30 students. The object of this research is the improvement of students' mathematical problem solving ability through the application of the Problem Based Learning learning model on SPLDV material at SMP Negeri 1 Stabat in the 2023/2024 school year. Based on the results of data analysis, the average initial test score was 47.11 with the number of students who reached mastery as many as 4 students (13.33%) and students who had not reached mastery as many as 26 students (86.67%). Then learning was carried out with the Problem Based Learning learning model in cycle I and there was an increase in the problem solving ability test with an average value of 63.44 with 19 students or as many as (63.33%). Then students who have not reached completeness are 11 students or as many as (36.67%). Then in cycle II there was an increase with the average value of the student problem solving ability test being 84.11, with a total completeness of 26 students or as many as (86.67%) and the number of students who had not reached completeness was 4 students or as many as (13.33%). The level of student completeness of the problem solving ability test given in cycle II reached the good category, therefore it can be said that learning has been achieved. Thus it can be said that the class has reached more than 85% of students who have been completed to solve problems. So it can be concluded that using the Problem Based Learning model can improve students' mathematical problem solving skills.